Perhitungan Harga Pokok Pesanan (HPP) Produk Trackpants D’goalsport dengan Metode Biaya Pesanan Pekerjaan - Miftahul Huda; Isna Isna; Purnama Sari Lase; Sopia Tiara Ramadhani S; Rifky Adhitia (Intellektika : Jurnal Ilmiah Mahasiswa, 2025)
Calculating the Cost of Goods Sold (COGS), also known as Job Order Costing (JOC), is a method of accumulating production costs for companies that manufacture goods based on specific orders. In this method, costs such as raw material costs, labor costs, and overhead costs are calculated separately for each order. By calculating COGS, companies can achieve efficiency in their expenditures and maximize production results to gain customer satisfaction. Therefore, this research aims to calculate the COGS for D’goalsport products so that the goods produced are efficient and generate profit for the business. The method used for calculating the Job Order Costing (COGS) in this paper is the Job Ordering Costing method. Based on the calculations performed, the Job Order Cost for each pair of pants produced is IDR 93.475. Thus, it can be concluded that the COGS for D’goalsport products still provides room for a Break-Even Point (BEP) cost of 50-100% according to market price.